1993
DOI: 10.1159/000108665
|View full text |Cite
|
Sign up to set email alerts
|

A Transcranial Doppler Study of Vasomotor Reactivity in Symptomatic Carotid Occlusion

Abstract: A group of 30 patients with symptomatic internal carotid artery (ICA) occlusion and different computed tomography (CT) patterns of cerebral ischemia (14 borderzone and/or terminal, 16 territorial) were studied by means of transcranial Doppler (TCD) to determine the relationship between vasomotor reactivity and the topography of the infarct on CT scan. The vasomotor reactivity was evaluated by assessing the mean flow velocity changes observed in the middle cerebral artery (MCA) after the longest possible apnea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…VMR% was evaluated by recording the percent differences in peak systolic BFV in each MCA at baseline and after Diamox administration. An intravenous (IV) injection of 1.0 g acetazolamide was given over 5 min, and the MCA BFVs were again measured with the ultrasound sample volume at the same depth 20 min later [6]. Table 1 Demographics and risk factor profiles in the cortical (CI) and subcortical (SI) brain infarct groups …”
Section: Vmr Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…VMR% was evaluated by recording the percent differences in peak systolic BFV in each MCA at baseline and after Diamox administration. An intravenous (IV) injection of 1.0 g acetazolamide was given over 5 min, and the MCA BFVs were again measured with the ultrasound sample volume at the same depth 20 min later [6]. Table 1 Demographics and risk factor profiles in the cortical (CI) and subcortical (SI) brain infarct groups …”
Section: Vmr Assessmentmentioning
confidence: 99%
“…VMR is defined as a shift between cerebral blood flow (CBF) or cerebral blood flow velocity (BFV) before and after administration of a potent vasodilatory stimulus test. VMR of the middle cerebral artery (MCA) was frequently assessed in patients with extracranial carotid occlusive disease, and several studies showed that highgrade stenosis or occlusion of the internal carotid artery (ICA) can significantly reduce VMR of the ipsilateral MCA [3][4][5][6]. Furthermore, the predictive value of impaired VMR for ischemic stroke occurrence was convincingly confirmed in subjects with carotid occlusive disease [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…CBF velocity (CBFV) measured on transcranial Doppler (TCD) in the major cerebral arteries reflects CBF, and is thus often used to assess vasomotor reactivity [2]. Reduced vasomotor reactivity has frequently been demonstrated in studies on patients with chronic extracranial carotid occlusive disease [3,4], and this correlates with the risk of stroke [5,6]. Only a few studies, however, exist on vasomotor response to hypercapnia assessed by change in CBFV in acute ischemic stroke patients who do not have carotid occlusive disease [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It remains controversial whether borderzone infarcts are due to impaired cerebral perfusion and whether territorial infarcts are caused by artery‐to‐artery emboli in case of occlusion of the internal carotid artery (Torvik and Skullerud, 1982; Bogousslavsky and Regli, 1986a; Weiller et al. , 1991a; Provinciali et al. , 1993; Baumgartner and Regard, 1994; Klijn et al.…”
Section: Introductionmentioning
confidence: 99%